3-D compact model for nanoscale junctionless triple-gate nanowire MOSFETs, including simple treatment of quantization effects. (October 2015) - Holtij, Thomas; Kloes, Alexander; Iñíguez, Benjamín
Abstract: In this work we briefly review our 2-D compact model for nanoscale junctionless (JL) double-gate (DG) MOSFETs and present and extension for 3-D triple-gate nanowire (TG-NW) devices. The model itself is physics-based and derived in closed-form. Important short-channel effects (SCEs) are covered by the model, as well as carrier quantization effects (QEs). The modeling of QEs in JL devices differs from their common treatment in inversion mode devices and therefore, requires some special attention. The model is verified versus TCAD simulations and measurement data, which were provide through the "SQWIRE" project, by the LETI in Grenoble, France. Additionally, important device characteristics such as symmetry around V ds = 0 V and continuity of the drain current I ds at derivatives of higher order (up to third order) are in focus of this work.